2015
DOI: 10.1159/000375536
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Urolithiasis in Patients with Crohn's Disease

Abstract: Background: The incidence of urinary tract calculi is thought to be higher in patients with inflammatory bowel disease (IBD) than that in the general population. However, few data are available about urolithiasis in patients with Crohn's disease (CD). We investigated the incidence of urolithiasis and the risk factors for urolithiasis in patients with CD. Methods: We examined the records of 387 patients with CD followed at Samsung Medical Center from July 2011 to June 2013. Evidence for the presence of calculi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…7 Most studies linking IBD with risk of urolithiasis are older or based on small or selected patient populations. [2][3][4][5][6]8 Hence, the magnitude of risk of urolithiasis in IBD remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…7 Most studies linking IBD with risk of urolithiasis are older or based on small or selected patient populations. [2][3][4][5][6]8 Hence, the magnitude of risk of urolithiasis in IBD remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 32 articles (n = 13,339,065 patients) were included in the qualitative (systematic review) and quantitative synthesis (meta-analysis). [12–16,21–47] Figure 1 shows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we found a nonsignificant association between developing urolithiasis and age (OR = 1.056, 95% CI: 0.947–1.164), type of IBD (OR = 1.056, 95% CI: 0.467–1.645), and 5-aminosalicylic acid concurrent medication (OR = 0.996, 95% CI: 0.976–1.016). Individual studies [ 29 , 33 , 35 , 36 , 38 , 39 ] showed that there was a significant association between developing urolithiasis and the disease duration of IBD (OR = 1.03, 95% CI: 1.01–1.05), the presence of fistula, fissure, or abscess (OR = 2.01, 95% CI: 1.32–3.07), existence of stenosis (OR = 1.82, 95% CI: 1.18–2.8), NSAID intake (OR = 2.334, 95% CI: 1.415–3.851), activity index (OR = 1.032, 95% CI: 1.018–1.045), active UC (OR = 4.2, 95% CI: 1.1–15), white race (OR = 1.49, 95% CI: 1.087–2.048), number of bowel resections (OR = 1.415, 95% CI: 1.17–1.71), and CD treatment period (OR = 1.076, 95% CI: 1.04–1.113), Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial species which can exchange Ox and convert this to formate have the potential to reduce the amount of Ox present in the GIT thereby reducing circulating CaOx. Increasing the abundance of species with these capabilities could be beneficial in patients suffering from CD as it has been reported that these patients have a 10-100 fold higher chance of developing kidney stones compared to healthy controls and patients with UC (Kim et al, 2015, Gaspar et al, 2016. Further investigations as to whether Flavonifractor spp.…”
Section: Discussionmentioning
confidence: 99%